Int. J. Adv. Res. Biol. Sci 2017
DOI: 10.22192/ijarbs.2017.04.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Docking Analysis of Potential Dipeptidyl peptidase - 4 (DPP-4) Inhibitors from Siddha formulation Pungampoo Chooranam for treating Diabetes mellitus

Abstract: Diabetes mellitus (DM) is a metabolic disorder characterized by chronic hyperglycemia or increased blood glucose levels with disturbances in carbohydrate, fat and protein metabolism resulting from absolute or relative lack of insulin secretion. The important pathogenic factors responsible for the development of metabolic disorder, insulin resistance, β-cells dysfunction, and finally diabetes are oxidative stress and tissue specific systemic inflammation. It was proven that drug which selectively inhibit the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…They reported that quercetin exhibited a good docking profile with tyrosine and AMP Kinase [24]. Various authors studied molecular docking of bioactive compounds, reported that quercetin as a potential drug candidate, and showed high binding affinity with target protein to synthesize anti-diabetic drug molecules [25][26][27]. The present study reports are reaffirmed that quercetin considered as the potential drug candidate for TCF7L2 protein.…”
Section: Resultssupporting
confidence: 78%
“…They reported that quercetin exhibited a good docking profile with tyrosine and AMP Kinase [24]. Various authors studied molecular docking of bioactive compounds, reported that quercetin as a potential drug candidate, and showed high binding affinity with target protein to synthesize anti-diabetic drug molecules [25][26][27]. The present study reports are reaffirmed that quercetin considered as the potential drug candidate for TCF7L2 protein.…”
Section: Resultssupporting
confidence: 78%
“…A common interaction was observed between Ser720, Ala732, Met733, Gln731, and Phe730 when coumarin lacked its hydrogen donor functions at the backbone structure. The quercetin interaction showed 50-60% similarity to that of sitagliptin [40].…”
Section: Discussionmentioning
confidence: 95%
“…8 The bioactive phyto components from Pungampoo chooranam tested against DPP4 results in significant anti-diabetic activity compared to standard sitagliptin using computational aided drug design software auto-dock Vina. 9 Another study also used the same computational auto dock vina tool for the analyses of ligand-receptor interaction. The phytochemical compounds like quercetin, isovitexin, synringin, mangiferin, purine 2,6 dione, etc., have been retrieved from the ZINC database docked against DPP4 PID: IJ2E.…”
mentioning
confidence: 99%